Scalable One-Pot - Liquid-Phase Oligonucleotide Synthesis for Model Network Hydrogels - Creusen, Guido (J Am Chem Soc, 2020)
Solid-phase oligonucleotide synthesis (SPOS) based on phosphoramidite chemistry is currently the most widespread technique for DNA and RNA synthesis, but suffers from scalability limitations and high reagent consumption. Liquid-phase oligonucleotide synthesis (LPOS) uses soluble polymer supports and has the potential of being scalable. However, at present, LPOS requires 3 separate reaction steps and 4-5 precipitation steps per nucleotide addition. Moreover, long acid exposure times during the deprotection step degrade sequences with high A-content (adenine) due to depurination and chain cleavage. In this work, we present the first one-pot liquid-phase DNA synthesis technique, which allows the addition of one nucleotide in a one-pot reaction of sequential coupling, oxidation and deprotection, followed by a single precipitation step. Furthermore, we demonstrate how to suppress depurination during the addition of adenine nucleotides. We showcase the potential of this technique to prepare high-purity 4-arm PEG-T(20) (T = thymine) and 4-arm PEG-A(20) building blocks in multi-gram scale. Such complementary 4-arm PEG-DNA building blocks reversibly self-assemble into supramolecular model network hydrogels, and facilitate the elucidation of bond lifetimes. These model network hydrogels exhibit new levels of mechanical properties (storage modulus, bond lifetimes) in DNA bonds at room temperature (melting at 44 °C), and thus open up pathways to next-generation DNA-materials programmable through sequence recognition and available for macroscale applications.